ILRI's research—Much more relevant for development - McDermott, John J. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), John McDermott, reflects on the evolution of ILRI's research over the past eight years and the future of livestock for development.